Understanding Teacher Work Discipline Through Instructional Leadership and Work Motivation: An Indonesian Elementary School Perspective - Lasminto, Lasminto; Khoiri, Nur; Ariyanto, Lilik (Papanda Publisher, 2025)
Teacher work discipline is fundamental to educational quality, yet persistent challenges exist in Indonesian elementary schools. This study examined the influence of instructional leadership and work motivation on teacher work discipline in Pedurungan District, Semarang City. A quantitative descriptive-correlational design was employed with 195 elementary school teachers selected through proportional random sampling. Data were collected using validated questionnaires measuring instructional leadership (α = 0.859), work motivation (α = 0.770), and teacher work discipline (α = 0.891). Multiple linear regression analysis was conducted following classical assumption testing. Instructional leadership significantly influenced teacher work discipline (t = 7.084, p < 0.001), as did work motivation (t = 3.383, p < 0.001). Simultaneously, both variables explained 34.4% of variance in teacher discipline (F = 50.541, p < 0.001), with 65.6% attributable to other factors. The regression equation Y = 16.472 + 0.065X₁ + 0.044X₂ indicated positive relationships between predictors and discipline. Findings validate integrated organizational behavior models, demonstrating that teacher discipline emerges from synergistic interactions between external leadership practices and internal motivational states. Results extend limited research on combined effects of leadership and motivation in non-Western educational contexts, suggesting comprehensive improvement strategies must address both principal instructional capacity and teacher motivational systems simultaneously rather than in isolation.